Lessons from China’s 48-h COVID-19 testing regime during the dynamic zero COVID policy period - Ali Cheshmehzangi; Zhaohui Su; Tong Zou; Zaheer Allam; Tian Tang (Discover Public Health)
Abstract During the pandemic, China’s dynamic zero-COVID policy received much support and criticism simultaneously. In 2022, most Chinese cities of medium to large size had to conduct regular mass testing, leading to a sort of 48-h/48 h COVID-19 testing regime that financially affected many local governments. Aside from financial implications and challenges, cities also faced spatial, institutional, and operational challenges. This practice stayed in place for months, and a territorial approach was considered in mass testing methods. Therefore, in this brief commentary paper, we look at the impacts at the city level, mainly that they had to be adaptive and dynamic during regular changes and policy formations at the national and provincial levels. The implementation that ought to occur at the municipal/city government level indicates multiple pressures beyond just financial challenges. During this period, cities’ debt increased and affected the provision or allocation of funding for other operations. This brief study shed light on these challenges from the development perspective, allowing us to reflect on some of the earlier issues and prepare better for any future events of such kind. The study contributes to previous and ongoing debate on city-level management, administrative support, and adaptive thinking in daily operations, particularly during disruptive events such as pandemics.